Anxiety in a regular day of work: A 24 hour psychophysiological investigation in young dentists with gender comparison - Queirolo, Luca; Bacci, Christian; Roccon, Andrea; Zanette, Gastone; Mucignat, Carla (Frontiers in Psychology, 2023)
Introduction and aim Dentistry is a highly demanding profession with a strong mental and physical involvement, possibly generating anxiety. Very few studies assessed psychophysiological activity in dentists, while none tried to relate it with gender during a routine working day. This study aims at evaluating correlations between gender, psychophysiological indexes, and psychological variables. Materials and methods Data were acquired at the Dental Clinic of the University of Padua on 20 healthy young dentists (10 M-10F) during a 24 h period of a working day. Physiological variables (measured with E4 Empatica) were electrodermal activity (EDA), heart rate variability (HRV) and heart rate (HR). Participants anxiety was measured through a self-reported scale on patient-relationship anxiety and through the Generalized Anxiety Disorder-7 Questionnaire (GAD-7). Results 5 (3F, 2 M) participants over 20 had a GAD-7 score ≥ 10. Female gender, in comparison to Male, was associated with higher perceived patient relationship anxiety (p = 0.002) and lower HRV (p-adj = 0.022). The gender Male, although being associated with lower level of self-reported anxiety (p = 0.002), showed an equal number of subjects with a GAD-7 score ≥ 10 (p = 0.371). No interaction between gender and EDA was found, nor an effect of GAD score on EDA, HRV and HR values. Higher values of EDA were found during sleep time; a difference between sleep time and working time EDA (p = 0.037) and a difference between sleep time and daytime (p = 0.0045). A different HR between sleep and all daytime (p < 0.001) was also highlighted. Conclusion 25% of dentists fell within generalized anxiety disorder diagnosis, compared to a maximum of 8.6% in the general population. A possible general biomarker of excessive stress response was measured: a shift of circadian sympathetic activity was found in dentists; a higher activity during sleep in comparison to working time and daytime. The Female gender was associated with higher perceived patient-approach anxiety, lower parasympathetic activity, and a comparable sympathetic activity to the Male gender, thus fostering a possible vulnerability to excessive stress. This study underlines the need to empower the psychological approach to stress and patient-relationship in dentistry.